Evaluation of southwestern Kansas native grasses - T.T. Marston; D.O. Yauk (Kansas Agricultural Experiment Station Research Reports, 2001)
Native grass samples were collected monthly for five years and analyzed for nutrient content. Crude protein and ADF content indicate that grass quality is highest in May and June, then steadily declines until October. Stocker operators may need to begin protein supplementation as early as July to sustain weight gains. Trace mineral values were erratic from year to year and month to month between and within years, indicating that trace mineral supplementation should probably be maintained throughout the grazing season.
Keywords: Cattlemen& #x27; s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Native grass; Protein; Minerals; Nutrition